2021
DOI: 10.3390/ijerph181910351
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Mobile Health Applications with Self-Management Behaviors among Adults with Chronic Conditions in the United States

Abstract: Background: Mobile applications related to health and wellness (mHealth apps) are widely used to self-manage chronic conditions. However, research on whether mHealth apps facilitate self-management behaviors of individuals with chronic conditions is sparse. We aimed to evaluate the association of mHealth apps with different types of self-management behaviors among patients with chronic diseases in the United States. Methods: This is a cross-sectional observational study. We used data from adult participants (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Whereas the other COPD apps appear to provide combinations of didactic education, symptoms tracking, exercise encouragement and collaborations with clinicians (Bentley et al 2020 ; Crooks et al 2020 ; Farmer et al 2017 ; Kwon et al 2018 ; North et al 2020 ; Park et al 2020 ; Vorrink et al 2016 , 2017 ; Wang et al 2021b ). Two key components that appear frequently across these apps are the interactive feedback and the possibility to collaborate with their healthcare teams, features well suited to optimize acceptability and implementation among patients (Blackstock and Roberts 2021 ; Morrison et al 2016 ; Wang et al 2021a ). However, the apps in these RCTs may have the potential to provide additional designs or features not discussed here as this study was limited to synthesizing the information that was inconsistently reported across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the other COPD apps appear to provide combinations of didactic education, symptoms tracking, exercise encouragement and collaborations with clinicians (Bentley et al 2020 ; Crooks et al 2020 ; Farmer et al 2017 ; Kwon et al 2018 ; North et al 2020 ; Park et al 2020 ; Vorrink et al 2016 , 2017 ; Wang et al 2021b ). Two key components that appear frequently across these apps are the interactive feedback and the possibility to collaborate with their healthcare teams, features well suited to optimize acceptability and implementation among patients (Blackstock and Roberts 2021 ; Morrison et al 2016 ; Wang et al 2021a ). However, the apps in these RCTs may have the potential to provide additional designs or features not discussed here as this study was limited to synthesizing the information that was inconsistently reported across studies.…”
Section: Discussionmentioning
confidence: 99%
“…MHealth apps have features to help users understand and manage their disease by providing monitoring and feedback, education, medication reminders and rehabilitation support (Fan and Zhao 2022 ; Wu et al 2020 ). Recent studies have explored the effectiveness and feasibility of incorporating mHealth apps into people’s self-care by modifying their behaviors (Hamine et al 2015 ; Iribarren et al 2021 ; Wang et al 2021a ). With the COVID-19 pandemic, interest in using mHealth apps increased significantly, as they were viewed as simple and accessible tools to safely promote virtual health (Dixit and Nandakumar 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently published recommendations by EULAR [ 6 ] highlight the importance of encouraging patient self-management strategies and the crucial role of digital formats [ 7 ]. As the large majority of patients with rheumatic and musculoskeletal diseases (RMDs) (91%) regularly uses smartphones [ 8 ], digital health application (DHA) represent a promising format to offer patients continuous, on-demand support in achieving disease remission.…”
Section: Introductionmentioning
confidence: 99%
“…Applications addressing chronic conditions have already shown benefits for patients with different chronic conditions. Several DHA have demonstrated the ability to improve outcomes in patients with obesity, depression, and diabetes [ 7 , 14 ]. Engaging patients with DHA has been proposed in several publications to change patient's health behaviors [ 15 ], enhance self-efficacy to manage symptoms [ 16 ], decrease health risk behaviors [ 17 ], and improve clinical outcomes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many barriers and facilitators that play a role in PP use [18][19][20]. Determining the current PP use status among patients of different races/ethnicities and identifying promoting factors of PP use may help patients gain better healthcare connections, improve self-care management of chronic diseases, and eventually improve patient healthcare outcomes [21][22][23]. Therefore, we aim to determine: 1) the PP use status, 2) the PP use associated with clinical outcomes (serum glycemic control and hospitalization), and 3) potential facilitators of PP use among diabetic patients of different races and ethnicities.…”
Section: Introductionmentioning
confidence: 99%